2017
DOI: 10.1021/acscentsci.7b00358
|View full text |Cite
|
Sign up to set email alerts
|

Nanoporous Thermosets with Percolating Pores from Block Polymers Chemically Fixed above the Order–Disorder Transition

Abstract: A lamellar diblock polymer combining a cross-linkable segment with a chemically etchable segment was cross-linked above its order–disorder temperature (TODT) to kinetically trap the morphology associated with the fluctuating disordered state. After removal of the etchable block, evaluation of the resulting porous thermoset allows for an unprecedented experimental characterization of the trapped disordered phase. Through a combination of small-angle X-ray scattering, nitrogen sorption, scanning electron microsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
68
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(80 citation statements)
references
References 40 publications
11
68
1
Order By: Relevance
“…Lightly cross-linked block copolymer networks re-assemble into organized morphologies upon cooling or solvent removal, but over a critical cross-link density, the networks are trapped in a disordered or disordered-like state. [73][74][75][76] Dynamic cross-links can also interfere with long-range order;…”
Section: S-8)mentioning
confidence: 99%
“…Lightly cross-linked block copolymer networks re-assemble into organized morphologies upon cooling or solvent removal, but over a critical cross-link density, the networks are trapped in a disordered or disordered-like state. [73][74][75][76] Dynamic cross-links can also interfere with long-range order;…”
Section: S-8)mentioning
confidence: 99%
“…Crosslinking strategies would be important to secure solvent resistance. Crosslinking examples have been reported [108][109][110] for membrane systems requiring block etching for pore formation and for microgels. [111] Pyrolysis of block copolymer films [112,113] could be extended to membranes.…”
Section: Self-assembly and Non-solvent Induced Phase Separation (Snips)mentioning
confidence: 99%
“…Within the experimentally relevant range of molecular weights, however, both experiments and simulations have shown that the ordered and disordered phases are both rather strongly segregated near the ODT, and contain nearly pure domains of A and B monomers [3][4][5]. In this regime, the disordered phase near the ODT appears to have a disordered bicontinuous network structure qualitatively similar to that of the bicontinuous microemulsion phase of some ternary systems [3,[6][7][8]. To describe this regime, one should use a theoretical approach that can describe strongly segregated structures.…”
mentioning
confidence: 96%